Work Posture as a Dominant Factor Associated with Low Back Pain among Administrative Employees in Bukittinggi City: Cross-Sectional Study - Siti Munawarah; Reza Olyverdi; Riri Segita (PT. Riset Press International, 2026)
Low back pain (LBP) is one of the most prevalent musculoskeletal disorders among office employees, particularly those exposed to prolonged static sitting and non-ergonomic working conditions. This condition not only affects individual health and functional capacity but also reduces work productivity and organizational performance. This study aimed to analyze factors associated with the occurrence of low back pain among administrative employees at the Department of Education and Culture of Bukittinggi City. An analytical observational study with a cross-sectional design was conducted from January to March 2025. A total of 40 administrative employees were recruited using total sampling based on predefined inclusion criteria. LBP was assessed using the Nordic Musculoskeletal Questionnaire (NMQ), while working posture was evaluated using the Rapid Office Strain Assessment (ROSA). Data were analyzed using univariate descriptive statistics, Chi-square tests for bivariate analysis, and Firth’s penalized logistic regression for multivariate analysis. A significance level of p < 0.05 was applied. The prevalence of LBP was 72.5% for minimal complaints and 27.5% for moderate complaints. Bivariate analysis showed that age (p = 0.017) and working posture (p = 0.019) were significantly associated with LBP, whereas gender (p = 0.307) and length of employment (p = 0.465) were not statistically significant. Multivariate analysis identified non-ergonomic working posture as the most dominant factor associated with LBP (OR = 5.50; 95% CI: 1.23–24.51). Working posture is the primary factor associated with low back pain among administrative employees in Bukittinggi City. Ergonomic improvements and posture education are strongly recommended to reduce the risk of LBP in office-based work environments.